2019
DOI: 10.1007/s11356-019-05153-7
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment of low-temperature biochar used as soil amendment on soil mesofauna

Abstract: Biochar as a carbon-rich highly porous substance has been proposed for use in agriculture and horticulture as a soil amendment. One of the main concerns of this application of biochar is its potential contamination with heavy metals (HMs) and polycyclic aromatic hydrocarbons. The aim of this research was to access the environmental risk of biochar used as a soil amendment on soil mesofauna (mites and springtails). We conducted both field and laboratory experiments with the use of wood-chip biochar from low-tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 62 publications
(70 reference statements)
0
11
0
Order By: Relevance
“…The toxicities of biochar were largely dependent on raw materials, pyrolysis temperature, and particle sizes of biochar (Liu et al 2019;Prodana et al 2019;Zhang et al 2019b, c). The elevated pH, PAHs and heavy metals contents, reactive oxygen species (ROS) levels upon the incorporation of biochar were the main reasons for the toxicities of biochar to soil biota and aquatic organisms (Gruss et al 2019;Liu et al 2019;Zhang et al 2019d). Hilber et al (2019) investigated the desorption resistance of PAHs (as an indirect measure of their bioaccessibility) in biochar as feed additive in cow ruminal liquid, and their results indicated that biochar containing < 10 mg/kg dw PAHs would not pose an increased unintended consequence to ruminants, which provided a novel and relative realistic method to assess these unintended health consequences of biochar (Hilber et al 2019).…”
Section: Biochar Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…The toxicities of biochar were largely dependent on raw materials, pyrolysis temperature, and particle sizes of biochar (Liu et al 2019;Prodana et al 2019;Zhang et al 2019b, c). The elevated pH, PAHs and heavy metals contents, reactive oxygen species (ROS) levels upon the incorporation of biochar were the main reasons for the toxicities of biochar to soil biota and aquatic organisms (Gruss et al 2019;Liu et al 2019;Zhang et al 2019d). Hilber et al (2019) investigated the desorption resistance of PAHs (as an indirect measure of their bioaccessibility) in biochar as feed additive in cow ruminal liquid, and their results indicated that biochar containing < 10 mg/kg dw PAHs would not pose an increased unintended consequence to ruminants, which provided a novel and relative realistic method to assess these unintended health consequences of biochar (Hilber et al 2019).…”
Section: Biochar Productionmentioning
confidence: 99%
“…To decrease the toxicities to microorganisms, it is required to select appropriate biochar as carriers for microorganism immobilization. The strong alkalinity of biochar caused by abundant minerals may also reduce microbial activity (Gruss et al 2019). This toxic effect could be reduced by washing biochar with acids and water to remove the minerals in biochar or selecting feedstocks which can result in neutral biochar.…”
Section: Perspectivesmentioning
confidence: 99%
“…Table 2. Soil properties after biochar application in oilseed rape and maize (sourced from Gruss et al [41]).…”
Section: Biochar Characteristic and Soil Propertiesmentioning
confidence: 99%
“…The chemical characteristic of biochar properties used in the experiment (sourced from Gruss et al[41]). …”
mentioning
confidence: 99%
“…The plant growth parameters were examined at different time intervals in field, and samples were further stored and analyzed under laboratory conditions. The low-temperature P. juliflora biochar used in the experimental study had a high carbon content and ability for nutrient storage, and these results were in close proximity with [16,20,24].…”
Section: Discussionmentioning
confidence: 87%